Multiple-Replicon Resistance Plasmids of Klebsiella Mediate Extensive Dissemination of Antimicrobial Genes - Wang, Xue; Zhao, Jianan; Ji, Fang; Chang, Han; Qin, Jiao; Zhang, Chenglin; Hu, Guocheng; Zhu, Jiayue; Yang, Jianchun; Jia, Zhongxin; Li, Gang; Qin, Jianhua; et al. (Frontiers in Microbiology, 2021)
Multiple-replicon resistance plasmids have become important carriers of resistance genes in Gram-negative bacteria, and the evolution of multiple-replicon plasmids is still not clear. Here, 56 isolates of Klebsiella isolated from different wild animals and environments between 2018 and 2020 were identified by phenotyping via the micro-broth dilution method and were sequenced and analyzed for bacterial genome-wide association study. Our results revealed that the isolates from non-human sources showed more extensive drug resistance and especially strong resistance to ampicillin (up to 80.36%). The isolates from Malayan pangolin were particularly highly resistant to cephalosporins, chloramphenicol, levofloxacin, and sulfamethoxazole. Genomic analysis showed that the resistance plasmids in these isolates carried many antibiotic resistance genes. Further analysis of 69 plasmids demonstrated that 28 plasmids were multiple-replicon plasmids, mainly carrying beta-lactamase genes such as blaCTX–M–15, blaCTX–M–14, blaCTX–M–55, blaOXA–1, and blaTEM–1. The analysis of plasmids carried by different isolates showed that Klebsiella pneumoniae might be an important multiple-replicon plasmid host. Plasmid skeleton and structure analyses showed that a multiple-replicon plasmid was formed by the fusion of two or more single plasmids, conferring strong adaptability to the antibiotic environment and continuously increasing the ability of drug-resistant isolates to spread around the world. In conclusion, multiple-replicon plasmids are better able to carry resistance genes than non-multiple-replicon plasmids, which may be an important mechanism underlying bacterial responses to environments with high-antibiotic pressure. This phenomenon will be highly significant for exploring bacterial resistance gene transmission and diffusion mechanisms in the future.